Peningkatan Kualitas Lulusan daan Daya Saing Perguruan Tinggi Swasta Berbasis Spiritual Capital : Studi Di Sumatera Utara - Radiman Radiman; Nadia Ika Purnama; Muhammad Andi Prayogi; Jufrizen Jufrizen; Maya Sari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Purpose - This study aims to produce a model for improving the quality of graduates and the competitiveness of private tertiary institutions based on spiritual capital by paying attention to and utilizing their spiritual capitalMethodology - This research was only conducted at the 15 best private universities in North Sumatra. The sample size for SEM using the Maximum Likelihood Estimation (MLE) estimation model is 100-200 samples. Data collection was carried out by distributing questionnaires. The data analysis method used in this study is factor analysis and the Structural Equation Modeling method using SEM-PLS softwareFindings - The results of the study show that there is a significant influence from Leadership and Good University Governance on Graduate Quality. There is a significant influence of Leadership and Good University Governance on Competitiveness. There is a significant influence of Leadership on Graduate Quality moderated by Spiritual Capital and there is a significant influence of the moderating effect of Spiritual Capital on the relationship between Good University Governance and Competitiveness.Originality/Novelty - The research model uses five (5) variables and applies the concept of mediation, where each relationship in the research model is analyzed with SEM-PLS.Implications - This study has shown that Spiritual Capital has a moderating effect on the influence. of Leadership and Good University Governance on Competitiveness. Starting from the results of this study, the recommendation for further research is to try to analyze or use the Spiritual Capital variable as an independent variable, not as a moderating variable.